Metabolic profiling of human melanoma cell lines with high and low metastatic capacity by 1H-NMR spectroscopy - Nima Rezvani Kakhki; Zita Hegedűs; József Tóvári; Arash Mirzahosseini; Béla Noszál; Márta Kraszni (PLoS ONE, 2026)
Background Melanoma is one of the most aggressive forms of skin cancer due to its high metastatic potential and mortality rate. Although understanding of metabolic reprogramming in melanoma has advanced, the connection between metabolic alterations and metastatic capacity remains incomplete. Aim This study aimed to characterize the metabolic profiles of human melanoma cell lines with high (HT168-M1) and low (WM983B) metastatic potential, and to compare them with each other and also with the metabolic profile of normal human fibroblasts (MRC-5), in order to identify key metabolites and metabolic pathways associated with metastatic behavior. Methods Non-targeted metabolomic profiling using ¹H-NMR spectroscopy was applied to hydrophilic extracts of the three cell lines. Multivariate statistical analyses (PCA and PLS-DA) were used to identify discriminating metabolites, and pathway analysis was performed to determine altered metabolic networks. Results Several metabolic pathways were significantly altered in melanoma cells compared to fibroblasts, including starch and sucrose metabolism, alanine, aspartate and glutamate metabolism, and glutathione metabolism. Metabolites showing more than two-fold differences included elevated UDP-glucose, ATP, glycerophosphocholine, GTP, creatine and glutathione in the melanoma cells, and reduced glucose, glutamine and 1-methylnicotinamide in fibroblasts. Comparison of the metabolites of melanoma cell lines with differing metastatic potential revealed changes in taurine and hypotaurine, β-alanine-, glutathione-, and amino acid metabolism. Metabolites showing the largest concentration changes were UDP-glucose, glutathione, NAD + , alanine and β-alanine. Conclusion Metabolomic profiling revealed distinct metabolic reprogramming between melanoma and normal fibroblasts, characterized by enhanced glycolysis and glutathione-dependent antioxidant defense. Highly metastatic melanoma cells demonstrated stronger redox adaptation and altered amino acid utilization, with elevated glutathione and glutamate and reduced NAD⁺ and pyruvate, indicating a metabolic shift toward oxidative stress resistance.